(3hGSWg GdYbO GdaQjO deG Mhi ef GdOQ GdfVjOs - (3eMeO Hf eMeO CHi GdSQhQ GdHcQi GdUOjbs; (3GHf CHj GdSQhQ , CHh GdSQhQ , CHh GdecGQe,J (B1087 (3g` s
(3ChdgG (B:s
(3hHYO aEfi deG CdaJ JGQjNi GdUZjQ GdeSei HGdefM GdQMeGfjI ai GdOhdI GdYKeGfjI s
(3BNQgG (B:s
(3jfJgi HPcQ ef hdi ef GdHcdQ jcjg Ydi eUQ GdeMeOjg s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B64 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B293s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B332 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs